Kajian Kesesuaian Lahan Tanaman Padi Sawah di Kecamatan Tanjung Selor Berbasis Sistem Informasi Geografis - Yoga Toyibulah; Fahrunsyah Fahrunsyah; Hasbiadi Hasbiadi (Department of Agribusiness, Halu Oleo University, 2022)
Evaluation of the level of land suitability for rice crops is used in planning agricultural land use so that inhibiting factors and solutions can be found in processing land to be planted. This study aims to evaluate the suitability of land for rice crop plants by implementing a geographic information system that facilitates and accelerates the data processing process so that research output can be used for consideration in land use in Tanjung Selor Subdistrict of Bulungan District. The variable used in this study was temperature, water availability (rainfall), oxygen availability (soil drainage conditions), root media (soil texture), erosion hazard (slope), flood hazard (inundation), and land use. Rainfall data are obtained from the analysis of climate factor data from 2011 to 2020, soil texture data is obtained from field observations and soil maps, slope data were obtained from the Digital Elevation Model in 2014, and land use data is obtained from land-use map interpretation in 2019. Of the seven parameters, four parameters are obtained from the map, namely rainfall map, soil map, slope map, and land use map. Soil sampling and observations in the field in 2021 are carried out to obtain data on temperature, flood hazards, and soil drainage conditions. Based on the results of the analysis of land suitability of rice in Tanjung Selor Subdistrict, 13,65% is suitable marginal, and 86,35% is not suitable for planting rice. Tanjung Selor Subdistrict is dominated by areas that cannot be planted on and can be planted, but the results are less than optimal.